Safety of EVO ICL Implantation With an Ophthalmic Viscosurgical Device-Free Technique in the Early 24 h After Surgery - Zhang, Zhe; Niu, Lingling; Zhao, Jing; Miao, Huamao; Chen, Zhuoyi; Shen, Yang; Chen, Xun; Ye, Yuhao; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2021)
Purpose: To compare the safety of the non-ophthalmic viscosurgical device (OVD) technique with that of the minimum OVD technique in EVO Implantable Collamer Lens (EVO-ICL) implantation. Methods: This prospective study evaluated a total of 100 eyes of 50 patients who underwent ICL implantation with the non-OVD technique and 80 eyes of 40 patients who underwent ICL implantation with the min-OVD technique. Preoperative and postoperative intraocular pressure (IOP) measurements were collected and analyzed at 1, 2, 3 and 24 hours. Visual acuity, corneal endothelial cell density (ECD), and corneal densitometry 24 hours postoperatively were evaluated. Results: No significant difference was found in visual outcomes (P=0.54) or ECD (P=0.78) between the two groups. The operation time was significantly shorter in the non-OVD group (P < 0.0001). The IOP was significantly higher at 1 hour (P < 0.0001), 2 hours (P<0.0001) and 3 hours (P=0.0045) postoperatively in the min-OVD group. The non-OVD group had significantly lower IOP than the min-OVD group at 1 hour (P=0.01) and 2 hours (P =0.013) postoperatively. The temporal corneal densitometry in the non-OVD group were significantly lower than those in the minimum group (P=0.0063) one day after surgery. Conclusion: The non-OVD technique is safe and efficient for ICL implantation. It can be a safer method of ICL implantation in that it completely eliminates ophthalmic viscoelastic devices related complications without causing additional complications.